Hybrid metal salts of dialkylphosphinic acid, process for their preparation, flame retardants and flame-retardant materials

CN122940790APending Publication Date: 2026-10-20NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610962043.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-30
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而二烷基次膦酸铁本身显示灰黄色,更重要的是,二烷基次膦酸铁长时间暴露空气后颜色更深,导致阻燃剂及阻燃制品发黄或发灰,造成产品质量低劣之不利感受

Benefits of technology

1、本发明提供了一种具有式(Ⅰ)结构的二烷基次膦酸杂化金属盐,通过将微量的铜离子嵌入到二烷基次膦酸盐或杂化盐的晶格中取代部分原有金属离子,形成非简单物理混合物的杂化晶体结构;这种微观结构层面的改变,提高了材料的热氧稳定性(高温下色变程度低)以及耐热性;相比于传统的铁离子掺杂体系,在达到相同的热氧稳定性或耐热性水平下,本发明所需的铜离子用量显著低于铁离子的用量。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention belongs to the technical field of flame-retardant polymer materials, specifically relating to dialkylphosphine acid hybrid metal salts and their preparation methods, flame retardants, and flame-retardant materials. The hybrid metal salt has the structure shown in formula (I): Formula (I), wherein R1, R2, R3, R4, R5, and R6 are each independently selected from C1-C1. 18 Straight-chain or branched alkyl groups, C6–C 12 Aromatic group; 0 ≤ x, y, z ≤ 1, and x + y + z = 1; M is selected from at least one of Group IIA, IIIA, IVA, VA metal elements, transition metal elements other than copper, and lanthanide metal elements; 0.9975 ≤ a ≤ 0.9999999, 0.0000001 ≤ b ≤ 0.0025, and a + b = 1. The dialkylphosphine hybrid metal salt provided by this invention is white in color and has high thermal and oxygen stability; its application in polymer materials can improve their thermal and oxygen stability and maintain the light-colored appearance of the materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of flame-retardant polymer materials technology, and relates to a class of dialkylphosphine hybrid metal salts and their preparation methods, flame retardants and flame-retardant materials. Background Technology

[0002] Dialkyl phosphonates have been used in flame retardant applications for polymer materials. However, for engineering plastics requiring high-temperature processing, the thermo-oxidative stability of dialkyl phosphonates is insufficient to ensure their long-term stability during the high-temperature mixing process for preparing flame-retardant polymers. Adverse changes in the flame retardant itself due to this thermo-oxidative degradation, such as yellowing, and the deterioration of the physical properties of the polymer material caused by the thermo-oxidative degradation of the flame retardant, need to be avoided.

[0003] In particular, for dialkylphosphine hybrid salts composed of different dialkylphosphine groups, although they have higher flame retardant efficiency than dialkylphosphinates composed of the same dialkylphosphine group, for example, in nylon and polyester, the former alone can enable polymer materials to achieve the excellent result of the highest flame retardant level UL94 V-0 expected by the industry, the thermo-oxidative stability of dialkylphosphine hybrid salts is lower than that of dialkylphosphinates. They are not only more prone to discoloration, but also more prone to causing degradation of polymer materials.

[0004] Chinese patent CN107641136B reports iron-doped dialkylphosphinates (excluding iron dialkylphosphinates) that exhibit higher thermo-oxidative stability compared to their iron-free counterparts. Chinese patent CN107637605B reports flame retardant compositions containing iron salts in dialkylphosphinates.

[0005] While the introduction of iron ions improves the thermo-oxidative stability of dialkylphosphinates, a relatively large amount of iron ions is required to achieve the desired effect. However, iron dialkylphosphinate itself is grayish-yellow, and more importantly, its color darkens further after prolonged exposure to air, causing flame retardants and flame-retardant products to yellow or gray, creating a negative perception of inferior product quality.

[0006] Therefore, it is a technical problem to both avoid the gray color caused by iron ions and improve the thermo-oxidative stability of dialkylphosphinates. Summary of the Invention

[0007] To address the aforementioned problems in the prior art, the present invention aims to provide dialkylphosphine hybrid metal salts and their preparation methods, flame retardants, and flame retardant materials, thereby overcoming the shortcomings of the prior art.

[0008] The present invention employs the following technical solutions to achieve its objective: One aspect of the present invention provides a dialkylphosphine hybrid metal salt, said dialkylphosphine hybrid metal salt being selected from at least one compound having the chemical formula shown in formula (I): Formula (I) Among them, R1, R2, R3, R4, R5, and R6 may be the same or different, and each is independently selected from C1-C2. 18 Straight-chain or branched alkyl groups, C6–C 12 Aromatic group; 0 ≤ x, y, z ≤ 1, and x + y + z = 1; M is a metallic element, which is selected from at least one of Group IIA, Group IIIA, Group IVA, Group VA, transition metals other than copper, and lanthanides. n is the valence state of M, selected from 1, 2, 3 or 4; m represents the valence state of copper, selected from 1 or 2; 0.9975≤a≤0.9999999, 0.0000001≤b≤0.0025, and a+b=1.

[0009] In equation (I), R1, R2, R3, R4, R5, and R6 may be the same or different, and each is independently selected from C1-C2. 18 Straight-chain or branched alkyl groups, C6–C 12 Aromatic groups include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, neopentyl, sec-pentyl, tert-pentyl, n-hexyl, isohexyl, sec-hexyl, tert-hexyl, n-heptyl, isoheptyl, sec-heptyl, tert-heptyl, n-octyl, isooctyl, sec-octyl, tert-octyl, n-nonyl, sec-nonyl, tert-nonyl, n-decyl, isodel, sec-decyl, tert-decyl, n-undecyl, isoundecyl, sec-undecyl, tert-undecyl, n-dodecyl, isododecyl, sec-dodecyl, tert-dodecyl, and phenyl.

[0010] Optionally, R1, R2, R3, R4, R5, and R6 are each independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, and tert-butyl.

[0011] Optionally, R1, R2, R3, R4, R5, and R6 are each independently selected from ethyl, n-propyl, isopropyl, n-butyl, isobutyl, and tert-butyl.

[0012] Optionally, R1, R2, R3, R4, R5, and R6 are each independently selected from ethyl, n-propyl, isopropyl, n-butyl, and isobutyl.

[0013] Optionally, R1, R2, R3, R4, R5, and R6 are each independently selected from ethyl, n-propyl, and isopropyl.

[0014] 0≤x,y,z≤1, meaning x,y, andz are all greater than or equal to 0 and less than or equal to 1, and x+y+z=1.

[0015] Optionally, of x, y, and z, at most two can be equal to 0, and the other can be 1.

[0016] Optionally, among x, y, and z, at most one is equal to 0, the other two are both greater than 0 and less than or equal to 1, and x+y+z=1.

[0017] Optionally, the lower limits of x, y, and z are independently selected from any value or a range between any two of 0, 0.02, 0.03, 0.04, 0.05, 0.10, 0.12, 0.14, 0.15, 0.20, 0.22, 0.25, 0.28, 0.30, 0.35, 0.38, 0.40, 0.41, 0.45, and 0.50, respectively, and the upper limits are independently selected from any value or a range between any two of 1, 0.97, 0.95, 0.90, 0.85, 0.80, 0.75, 0.70, 0.65, 0.64, 0.60, 0.55, and 0.50, respectively.

[0018] In this application, the values ​​of x, y, and z in formula (I) do not consider the amount of phosphorus-containing impurities other than dialkylphosphinates, and x + y + z = 1. All other phosphorus-containing impurities are not included in the normalization calculation of x, y, and z. Flame retardants with the composition of formula (I) may contain trace amounts of other phosphorus-containing impurities. Due to impurities in raw materials or impurities generated during the synthesis process, some trace amounts of phosphates, phosphites, alkylphosphinates, alkylphosphinates, etc., may exist in the flame retardant. However, as long as the total molar amount of all these other phosphorus-containing impurities does not exceed 10% of the total phosphorus molar amount, it does not affect the normal operation of the flame retardant with the composition of formula (I). Therefore, these impurities are not included in the calculation range of x, y, and z values.

[0019] In this embodiment of the application, the ratio of x, y, and z in formula (Ⅰ) can be obtained by alkaline or acid hydrolysis of the flame retardant, using... 31 P-NMR (nuclear magnetic resonance) is used to determine this. For example, when R1=R2=R3 is ethyl and R4=R5=R6 is propyl, the diethylphosphine ion, ethylpropylphosphine ion, and dipropylphosphine ion have different... 31 The chemical shift of P, in 31In most cases, the P-NMR spectrum shows independent peaks, with the peak areas corresponding to the molar concentrations of their respective dialkylphosphine ions. Some dialkylphosphine ions with the same chemical formula may have isomers, thus exhibiting different peaks in the P-NMR spectrum. When calculating the x, y, and z values, these isomers are grouped together. For example, when R1, R2, and R3 are ethyl, and R4, R5, and R6 are propyl, the resulting dialkylphosphine hybrid salt... 31 The P-NMR spectrum will show multiple sets of peaks, corresponding to diethylphosphine ions, ethyl-n-propylphosphine ions, ethyl-isopropylphosphine ions, di-n-propylphosphine ions, n-propyl-isopropylphosphine ions, and diisopropylphosphine ions, respectively. The molar concentration of diethylphosphine ion corresponds to x, the sum of the molar concentrations of ethyl-n-propylphosphine ions and ethyl-isopropylphosphine ions (collectively referred to as the molar concentration of ethylpropylphosphine ions) corresponds to y, and the sum of the molar concentrations of di-n-propylphosphine ions, n-propyl-isopropylphosphine ions, and diisopropylphosphine ions (collectively referred to as the molar concentration of dipropylphosphine ions) corresponds to z. These three values ​​are the values ​​of x, y, and z. In some cases, telomerized dialkylphosphine ions are present. These are present in very small quantities and their chemical shifts are close to those of the corresponding dialkylphosphine ions; therefore, they are included in the integration of the corresponding dialkylphosphine ions.

[0020] Optionally, the Group IIA metal element is selected from at least one of Be, Mg, Ca, Sr, and Ba; the Group IIIA metal element is Al; the Group IVA metal element is Sn; the Group VA metal element is Sb; the transition metal element other than copper is selected from at least one of Fe, Zn, Ti, Zr, and Mn; and the lanthanide metal element is Ce.

[0021] Further, optionally, the metallic element is selected from at least one of Al, Zn, Ca, and Fe.

[0022] Alternatively, the metallic element may be Al, with n=3.

[0023] In this application, 0.9975 ≤ a ≤ 0.9999999, 0.0000001 ≤ b ≤ 0.0025, and a + b = 1. If the b value is too low, the copper ion concentration is low, and its effect on improving the thermo-oxidative stability of dialkylphosphinates is not significant. If the b value is too high, the copper ion concentration is high, and its effect on improving the thermo-oxidative stability of dialkylphosphinates tends to stabilize, but excessive copper ions will cause discoloration.

[0024] Optionally, the lower limit of b is selected from any one value or any two values ​​among 0.0000001, 0.0000002, 0.0000003, 0.0000004, 0.0000005, 0.0000006, 0.0000007, 0.0000008, 0.0000009, 0.000001, 0.000002, 0.000005, 0.000007, 0.000009, 0.00001, and 0.00002.

[0025] Optionally, the upper limit of b is selected from 0.00003, 0.00004, 0.00005, 0.00006, 0.00007, 0.00008, 0.00009, 0.0001, 0.0002, 0.0003, 0.0004, 0.0005, 0.0006, 0.0007, 0.0008, 0.0009. The value is any one of the following: 0.0010, 0.0011, 0.0012, 0.0013, 0.0014, 0.0015, 0.0016, 0.0017, 0.0018, 0.0019, 0.0020, 0.0021, 0.0022, 0.0023, 0.0024, 0.0025, or any value between any two values.

[0026] Optionally, 0.9985≤a≤0.999999, 0.000001≤b≤0.0015, and a+b=1.

[0027] Optionally, 0.999≤a≤0.999995, 0.000005≤b≤0.001, and a+b=1.

[0028] Optionally, 0.9995≤a≤0.999995, 0.000005≤b≤0.0005, and a+b=1.

[0029] Optionally, 0.99975≤a≤0.999995, 0.000005≤b≤0.00025, and a+b=1.

[0030] Optionally, 0.9998≤a≤0.99999, 0.00001≤b≤0.0002, and a+b=1.

[0031] Optionally, 0.99985≤a≤0.99998, 0.00002≤b≤0.00015, and a+b=1.

[0032] Optionally, 0.99991≤a≤0.99998, 0.00002≤b≤0.00009, and a+b=1.

[0033] Optionally, 0.99784≤a≤0.999991, 0.000009≤b≤0.00216, and a+b=1.

[0034] The dialkylphosphonic acid hybrid metal salts in this application are not simple physical mixtures of different dialkylphosphonic acid metal salts, but rather trace amounts of copper ions that are inserted into the crystal lattice of the dialkylphosphonate or hybrid salt by substituting the metal ions of the latter.

[0035] Surprisingly, although pure dialkylphosphine copper is colored, such as diethylphosphine copper being blue, the dialkylphosphine hybrid copper salt prepared by trace doping with copper ions in this application remains white. More importantly, this hybrid copper salt exhibits excellent color stability during long-term storage, consistently maintaining its white color. In contrast, pure diethylphosphine iron is gray, and the dialkylphosphine hybrid iron salt with added iron ions appears pale gray, darkening during storage and affecting the product's appearance.

[0036] A second aspect of this application provides a method for preparing the above-mentioned dialkylphosphine hybrid metal salt, the method comprising: The material containing a mixture of metal sources A and M and a copper source is reacted in an aqueous phase to obtain the dialkylphosphine hybrid metal salt; The mixture A contains R1-based and R2-based hypophosphonic acids and / or their alkali metal salts, R3-based and R4-based hypophosphonic acids and / or their alkali metal salts, and R5-based and R6-based hypophosphonic acids and / or their alkali metal salts.

[0037] Optionally, the reaction conditions are: temperature 0~250℃, pressure 0.1~10 MPa, and time 0.01~20h. Optionally, the reaction temperature is any value or a range between any two of 0℃, 10℃, 20℃, 30℃, 40℃, 50℃, 60℃, 70℃, 80℃, 90℃, 100℃, 110℃, 120℃, 130℃, 140℃, 150℃, 160℃, 170℃, 180℃, 190℃, 200℃, 210℃, 220℃, 230℃, 240℃, and 250℃; the reaction pressure is 0.1MPa, 0.5MPa, 1MPa, or 2MPa. The pressure is any value or a range between any two of the following: Pa, 3 MPa, 4 MPa, 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa, and 10 MPa; the reaction time is any value or a range between any two of the following: 0.01 h, 0.05 h, 0.1 h, 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, and 20 h.

[0038] Optionally, the reaction is carried out at a pH of 0 to 5. Optionally, the reaction is carried out at any pH value of 0, 1, 2, 3, 4, 5, or a range between any two.

[0039] Optionally, when the metal element is Al, the pH of the reaction is 0 to 4, preferably 1 to 3.5, and more preferably 2.3 to 3.3.

[0040] Specifically, if the pH of the above reaction is too low, there will be little precipitation; if the pH is too high, metal ion hydroxides will be generated, introducing impurities.

[0041] Optionally, the metal source M is one or more of the following: sulfate or hydrate of metal M, chloride or hydrate of metal M, and nitrate or hydrate of metal M.

[0042] Optionally, the copper source is one or more of copper sulfate or its hydrate, copper chloride or its hydrate, copper oxide, copper hydroxide, copper nitrate or its hydrate, cuprous oxide (Cu2O), basic copper carbonate (Cu2(OH)2CO3), cuprous chloride, and cuprous sulfide (Cu2S).

[0043] Optionally, the copper source is one or more of copper sulfate or its hydrate, copper chloride or its hydrate, and cuprous chloride.

[0044] Optionally, the molar ratio of the following components—R1-based R2-based phosphonic acid and / or its alkali metal salt, R3-based R4-based phosphonic acid and / or its alkali metal salt, R5-based R6-based phosphonic acid and / or its alkali metal salt, the number of moles of M in the M metal source, and the number of moles of copper in the copper source—is or approximately x:y:z:(1 / n*a):(1 / m*b). That is, the amounts of R1-based R2-based phosphonic acid and / or its alkali metal salt, R3-based R4-based phosphonic acid and / or its alkali metal salt, R5-based R6-based phosphonic acid and / or its alkali metal salt, the M metal source, and the copper source are controlled such that the molar ratio of the R1-based R2-based phosphonic acid structural units, R3-based R4-based phosphonic acid structural units, R5-based R6-based phosphonic acid structural units, the M element, and the Cu element in the resulting dialkylphosphonic acid hybrid metal salt is or approximately x:y:z:(1 / n*a):(1 / m*b).

[0045] The mixture A can be prepared by reacting well-known hypophosphite and / or its alkali metal salt with one or more corresponding olefins in the presence of a free radical initiator, or by a mixture of respective dialkylphosphino acids and / or their alkali metal salts.

[0046] The free radical initiator is selected from at least one of azo initiators, peroxide initiators, and photoinitiators. The amount of free radical initiator added can be determined according to actual needs.

[0047] A third aspect of this application provides a flame retardant selected from at least one of the above-described dialkylphosphine hybrid metal salts and dialkylphosphine hybrid metal salts prepared according to the above method.

[0048] In actual reactions, due to the addition reaction of hypophosphoric acid and / or its alkali metal salts with alkenes under free radical initiation, some side reactions are unavoidable, generating phosphorous impurities such as phosphorous acid, phosphoric acid, alkylphosphonic acid, alkylphosphinoacid, and / or their alkali metal salts. Therefore, optionally, the flame retardant also contains at least one phosphorus-containing impurity selected from phosphates, phosphites, alkylphosphonates, alkylphosphinoacids, etc., wherein the molar content of these phosphorus-containing compounds in the flame retardant is less than or equal to 10%, and the molar number of the flame retardant is calculated based on the molar number of phosphorus elements contained therein. Their content can be calculated by the peak area of ​​the corresponding chemical shift in the phosphorus NMR spectrum.

[0049] The fourth aspect of this application provides a flame-retardant material comprising a flame retardant P and a thermoplastic polymer material; wherein the flame retardant P is selected from at least one of the above-mentioned flame retardants.

[0050] Optionally, the flame retardant P has a mass content of 1-35% in the flame retardant material.

[0051] Specifically, the amount of flame retardant P used depends on the specific thermoplastic polymer material.

[0052] Optionally, the flame retardant P has a mass content of 3-20% in the flame retardant material.

[0053] Optionally, the thermoplastic polymer material has a mass content of 65-95 wt% in the flame retardant material.

[0054] Optionally, the flame retardant material further includes functional additives; the functional additives are selected from at least one of reinforcing agents, anti-dripping agents, stabilizers, pigments, dyes, char-forming catalysts, dispersants, nucleating agents, inorganic fillers, and antioxidants.

[0055] Preferably, the functional additive in the flame retardant material has a mass content of 5-40%.

[0056] Optionally, the reinforcing agent is selected from at least one of glass fiber, carbon fiber, aramid fiber, and basalt fiber. The anti-dripping agent is selected from fluoropolymers, such as polytetrafluoroethylene (PTFE), for example, Teflon® PTFE. The stabilizer is selected from heat stabilizers and / or light stabilizers. The antioxidant is at least one of hindered phenolic antioxidants (such as antioxidant 1010, antioxidant 1076) and phosphite antioxidants (such as antioxidant 168). The pigment or dye is selected from at least one of inorganic or organic polymer toning powders, such as titanium dioxide (titanium white), carbon black, zinc oxide, iron oxide red, etc. The char-forming catalyst is selected from at least one of phenolic resin, porous thermopolymer, zeolite, montmorillonite, melamine and its derivatives, and zinc borate. The dispersant is at least one of stearic acid and its metal salts (such as zinc stearate, calcium stearate), ethylene bis-stearamide (EBS), silane coupling agents, titanate coupling agents, and polyethylene wax. The nucleating agent is selected from at least one of inorganic nucleating agents (such as talc) and organic nucleating agents (such as sodium benzoate, organophosphate nucleating agents, and sorbitol acetal derivatives). The inorganic filler is selected from at least one of mica, calcium carbonate, calcium oxide, and silica.

[0057] Optionally, the flame retardant material further includes a flame retardant Q; the flame retardant Q is selected from at least one of nitrogen-based flame retardants and boron-based flame retardants.

[0058] Optionally, the nitrogen-based flame retardant is selected from at least one of melamine cyanurate, melamine polyphosphate, and ammonium polyphosphate; the boron-based flame retardant is selected from zinc borate.

[0059] Optionally, the flame retardant Q has a mass content of 0.5-20% in the flame retardant material.

[0060] In this application, thermoplastic polymers refer to plastics that soften upon heating and harden upon cooling. Optionally, the thermoplastic polymer is selected from at least one of polyamides and polyesters.

[0061] Optionally, the polyamide is selected from at least one of aliphatic polyamide, aromatic polyamide, semi-aromatic polyamide, and copolymers of semi-aromatic polyamide and aliphatic polyamide.

[0062] According to common knowledge in this field, polyamide, also known as nylon, is a general term for polymers whose structural units contain -NH-C(O)- amide groups. It is synthesized through condensation or ring-opening reactions of one or more dicarboxylic acids and one or more diamines, and / or one or more amino acids, and / or one or more lactams. Based on the composition of its main chain, polyamides are generally classified into aliphatic polyamides, aromatic polyamides, and semi-aromatic polyamides. Semi-aromatic polyamides refer to those whose synthetic monomers contain at least one aromatic group in their structure.

[0063] Optionally, the semi-aromatic polyamide can be prepared from any one or more aromatic dicarboxylic acids and any one or more aliphatic diamines, or from any one or more aromatic diamines and any one or more aliphatic dicarboxylic acids. One or more of dicarboxylic acids, diamines, lactams, and amino acids can also be added to the system to prepare polyamide copolymers with corresponding properties. The added dicarboxylic acid is an aromatic dicarboxylic acid and / or an aliphatic dicarboxylic acid; the added diamine is an aromatic diamine and / or an aliphatic diamine; the added lactam can be an aliphatic or aromatic lactam. The added amino acid can be an aromatic or aliphatic amino acid.

[0064] Optionally, the semi-aromatic polyamide is prepared from one or more aromatic dicarboxylic acids selected from terephthalic acid, isophthalic acid and naphthalic acid, and one or more aliphatic diamines selected from butanediamine, hexamethylenediamine, octanediamine, decanediamine and 2-methylpentanediamine.

[0065] Optionally, the semi-aromatic polyamide is prepared from aliphatic diamines, aromatic dicarboxylic acids, and aliphatic dicarboxylic acids.

[0066] Optionally, the semi-aromatic polyamide is prepared from an aliphatic diamine and an aromatic dicarboxylic acid; optionally, an aliphatic dicarboxylic acid may also be added, wherein the molar fraction of the aliphatic dicarboxylic acid accounts for 0 to 45% of the total molar fraction of the dicarboxylic acid, i.e., the molar number of aliphatic dicarboxylic acid / (the molar number of aliphatic dicarboxylic acid + the molar number of aromatic dicarboxylic acid) = 0 to 45%.

[0067] Optionally, the aromatic dicarboxylic acid is selected from one or more of terephthalic acid, isophthalic acid, and naphthalic acid; the aliphatic diamine is selected from one or more of butanediamine, hexamethylenediamine, octanediamine, decanediamine, and 2-methylpentanediamine; and the aliphatic dicarboxylic acid is selected from one or more of succinic acid, succinic acid, sebacic acid, and octanoic acid.

[0068] Optionally, the polyamide may be selected from poly(hexamethylene terephthalamide) (abbreviated as PA6T), poly(hexamethylene isophthalamide) (abbreviated as PA6I), terephthalic acid / hexamethylenediamine / caprolactam copolymer (abbreviated as PA6T / 6), terephthalic acid / hexamethylenediamine / adipic acid copolymer (abbreviated as PA6T / 66), terephthalic acid / hexamethylenediamine / adipic acid / isophthalic acid copolymer (abbreviated as PA6T / 6I / 66), poly(nonadiamine terephthalamide) (abbreviated as PA9T), poly(hexamethylene terephthalamide), and poly(hexamethylene terephthalamide). One or more of the following: phthaloyl decanediamine (abbreviated as PA10T), poly(terephthaloyl dodecanediamine) (abbreviated as PA12T), terephthalic acid / hexamethylenediamine / dodecanoic acid copolymer (abbreviated as PA6T / 12), poly(m-phenylene adipamide) (abbreviated as MXD6), terephthalic acid / hexamethylenediamine / 2-methylpentanediamine copolymer (abbreviated as PA6T / 2-MPMDT), and terephthalic acid / 2,2,4-trimethylhexamethylenediamine / 2,4,4-trimethylhexamethylenediamine copolymer.

[0069] Optionally, the aliphatic polyamide is selected from at least one of polyamide 6, polyamide 66, and copolymers of polyamide 6 and polyamide 66.

[0070] Optionally, the semi-aromatic polyamide is selected from polyphthalamide (PPA).

[0071] Optionally, the polyester is selected from polybutylene terephthalate (PBT).

[0072] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention provides a dialkylphosphine hybrid metal salt with the structure of formula (I). By embedding a trace amount of copper ions into the crystal lattice of the dialkylphosphine acid salt or hybrid salt to replace part of the original metal ions, a hybrid crystal structure that is not a simple physical mixture is formed. This change at the microstructure level improves the thermal and oxygen stability (low degree of color change at high temperature) and heat resistance of the material. Compared with the traditional iron ion doping system, the amount of copper ions required by this invention is significantly lower than the amount of iron ions to achieve the same level of thermal and oxygen stability or heat resistance.

[0073] 2. Although pure dialkylphosphine copper has color, the dialkylphosphine hybrid copper salt prepared by micro-doping with copper ions in this application is still white; more importantly, the hybrid copper salt exhibits excellent color stability during long-term storage, always maintaining a white appearance, thus eliminating the negative commercial visual impact caused by poor color.

[0074] 3. When the dialkylphosphine hybrid metal salt with the composition of formula (Ⅰ) provided by the present invention is used as a flame retardant in polymer materials, it not only endows the materials with excellent flame retardant properties, but also improves the thermal and oxygen stability of the materials, broadens the high-temperature processing window of the materials, and the copper ion concentration required to improve the thermal and oxygen stability of flame-retardant polymer materials is lower than that of iron ions, and the color of the flame-retardant polymer materials is lighter.

[0075] 4. The present invention introduces trace amounts of copper, which can produce a significant "synergistic enhancement effect" with the main metal salt lattice and multi-phosphonate groups, greatly improving the heat resistance of the flame retardant. Attached Figure Description

[0076] Figure 1 The graph shows the test results of diethylphosphine-ethylpropylphosphine-dipropylphosphine hybrid aluminum salt (x=0.22) in a muffle furnace at 300°C for Examples 1-14. Figure 2 The graph shows the test results of diethylphosphine-ethylpropylphosphine-dipropylphosphine hybrid aluminum salt (x=0.41) in a muffle furnace at 300°C for Examples 15-19. Figure 3 The graph shows the test results of diethylphosphino-ethylpropylphosphino-dipropylphosphino-aluminum hybrid salts (x=0.60) in a muffle furnace at 300°C for Examples 20-24. Figure 4 The graph shows the test results of diethylphosphine hybrid aluminum salt (x=1) in a muffle furnace at 300°C for Examples 25-29; Figure 5 The graph shows the test results of the diethylphosphine-ethylisobutylphosphine-diisobutylphosphine hybrid aluminum salts in Examples 30-32 at 300°C in a muffle furnace. Figure 6 Color photographs of flame-retardant nylon prepared with flame retardants according to different embodiments. Detailed Implementation

[0077] In the description of this invention, unless otherwise stated, numerical ranges, such as "0~250", represent abbreviated representations of any combination of real numbers between 0 and 250, including both 0 and 250, and so on. "Multiple" includes two or more types, and can be two, three, four, five, or more.

[0078] The technical solution of the present invention will be further described and illustrated below with reference to specific embodiments and accompanying drawings. It should be understood that the specific embodiments described herein are only for the purpose of helping to understand the present invention and are not intended to limit the specific scope of the present invention. Furthermore, the accompanying drawings used herein are merely for better illustrating the content disclosed in the present invention and do not limit the scope of protection. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used in the art, and the methods used in the embodiments are all conventional methods in the art.

[0079] In the following embodiments, the raw materials are sourced as follows: A mixture of sodium diethylphosphonate, sodium ethylpropylphosphonate, and sodium dipropylphosphonate: prepared according to the method of patent CN116947918A.

[0080] Sodium diethylphosphonate solution: prepared according to the method of Comparative Example 2 in patent CN116947918A.

[0081] A mixture of sodium diethylphosphonate, sodium ethyl isobutylphosphonate, and sodium diisobutylphosphonate: prepared according to the method of patent CN115974915A.

[0082] Aluminum sulfate octahydrate: Sinopharm Chemical Reagent Co., Ltd.

[0083] Ferric chloride: Sinopharm Chemical Reagent Co., Ltd.

[0084] Copper sulfate pentahydrate: Sinopharm Chemical Reagent Co., Ltd.

[0085] PA66 (also known as polyamide 66 or nylon 66): Zytel@70G33L NC010, with a glass fiber content of 33% by weight, manufactured by DuPont, USA.

[0086] Test method: Flame retardant thermal-oxidative stability (color test) Place 0.1 g of sample into a 10 mL crucible, cover it, and place it in a muffle furnace. Start heating from room temperature to 300 °C at a heating rate of 10 °C per minute. After reaching 300 °C, hold at that temperature for the predetermined time. Then, turn off the heating source, remove the crucible, open the lid, and observe the sample color. The darker the color, the more severe the thermo-oxidative degradation.

[0087] Heat resistance of flame retardants (thermogravimetric analysis) Take approximately 5 mg of sample and heat it in an air-conditioned thermogravimetric analyzer (TGA) from room temperature to 600 °C at a rate of 10 °C / min. Record the temperature at which 2% weight loss occurs. Higher temperatures indicate better heat resistance.

[0088] Flame-retardant nylon thermo-oxidative stability Flame retardant and nylon 66 (containing 33% glass fiber) are mixed in a ratio of 12.5:87.5, and then extruded through a single screw extruder at a temperature of 260 to 300°C. After cooling in a water bath, the mixture is granulated and thoroughly dried to obtain flame retardant nylon.

[0089] a) Color of flame-retardant nylon: Flame-retardant nylon granules are injection molded at 280°C using an injection molding machine, and the color change is observed.

[0090] b) Processing window of flame-retardant nylon: Since the lower limit of the processing window of flame-retardant nylon is unaffected, only the decomposition of flame-retardant nylon at the upper limit is measured. Therefore, its weight loss at a specified temperature (300°C) is tested. The lower the weight loss rate, the better the thermo-oxidative stability of the flame-retardant nylon and the wider its processing window. Specifically, the test is performed using TGA: The flame-retardant polymer is pressed into a 0.2 mm thick sheet using a flat vulcanizing machine at 280°C. Approximately 8 mg of the sheet sample is cut and heated to 300°C in an air atmosphere at a rate of 10°C / min in a TGA chamber. This temperature is maintained for 1 hour, and the percentage of weight loss is recorded.

[0091] Metal ion content: determined using inductively coupled plasma optical emission spectrometry (ICP-OES).

[0092] Example 1: Aluminum salt of diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid (x=0.22, y=0.64, z=0.14) 71 g of a mixed aqueous solution of sodium diethylphosphonate (22.37% mol total phosphorus), sodium ethylpropylphosphonate (63.31% mol total phosphorus), and sodium dipropylphosphonate (14.32% mol total phosphorus) (containing 0.1855 mol total phosphorus) was mixed with a 30% aqueous solution containing 21.09 g of aluminum sulfate octadecylhydrate. The reaction temperature was controlled at 70 °C, resulting in a large amount of precipitate. The pH was adjusted to 3.0, and the reaction was stopped after 0.5 hours. The resulting reaction solution was filtered, and the filter cake was washed with deionized water until the pH was > 4.5. The filter cake was dried at 120 °C to obtain 24.4 g of a white solid of aluminum diethylphosphonate-ethylpropylphosphonate-dipropylphosphonate (x = 0.22, y = 0.64, z = 0.14) with the structure shown in formula (I).

[0093] Example 2: A hybrid aluminum-iron salt of diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid containing 11 ppm iron ions (x=0.22, y=0.64, z=0.14). 71 g of a mixed aqueous solution containing sodium diethylphosphonate (22.37% mol total phosphorus), sodium ethylpropylphosphonate (63.31% mol total phosphorus), and sodium dipropylphosphonate (14.32% mol total phosphorus) (containing 0.1855 mol total phosphorus) was mixed with a 30% aqueous solution containing 21.09 g of aluminum sulfate octadecylhydrate and 0.1478 g of a 0.5% aqueous solution of ferric chloride. The reaction temperature was controlled at 70°C, resulting in a large amount of precipitate. The pH was adjusted to 3.0, and the reaction was stopped after 0.5 hours. The resulting reaction solution was filtered, and the filter cake was washed with deionized water until the pH was > 4.5. The filter cake was dried at 120°C to obtain 24.25 g of a white solid with the structure shown in formula (I) having x = 0.22, y = 0.64, z = 0.14, containing 11 ppm of iron ions.

[0094] Example 3: Diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid hybrid aluminum iron salt containing 28 ppm iron ions (x=0.22, y=0.64, z=0.14) Following the method of Example 2, the mass of the ferric chloride aqueous solution was changed to 0.4434 g, resulting in 24.30 g of a white solid with x=0.22, y=0.64, z=0.14 in the structure shown in Formula (I), containing 28 ppm of iron ions.

[0095] Example 4: A hybrid aluminum-iron salt containing 49 ppm iron ions of diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid (x=0.22, y=0.64, z=0.14). Following the method of Example 2, the mass of the ferric chloride aqueous solution was changed to 0.739 g, resulting in 24.39 g of a white solid with x=0.22, y=0.64, z=0.14 in the structure shown in Formula (I), containing 49 ppm of iron ions.

[0096] Example 5: Diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid hybrid aluminum iron salt containing 96 ppm iron ions (x=0.22, y=0.64, z=0.14) Following the method of Example 2, the mass of the ferric chloride aqueous solution was changed to 1.478 g, resulting in 24.17 g of a white solid with x=0.22, y=0.64, z=0.14 in the structure shown in Formula (I), containing 96 ppm of iron ions.

[0097] Example 6: Diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid hybrid aluminum iron salt containing 487 ppm iron ions (x=0.22, y=0.64, z=0.14) Following the method of Example 2, 0.037 g of ferric chloride solid was used instead of its aqueous solution to obtain 24.28 g of a white solid with x=0.22, y=0.64, z=0.14 in the structure shown in Formula (I), which contains 487 ppm of iron ions.

[0098] Example 7: Diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid hybrid aluminum iron salt containing 971 ppm iron ions (x=0.22, y=0.64, z=0.14) Following the method of Example 2, 0.0739 g of ferric chloride solid was used instead of its aqueous solution to obtain 24.15 g of a white solid with x=0.22, y=0.64, z=0.14 in the structure shown in Formula (I), which contains 971 ppm of iron ions.

[0099] Example 8: A hybrid aluminum-copper salt of diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid containing 2 ppm copper ions (x=0.22, y=0.64, z=0.14). 71 g of a mixed aqueous solution containing sodium diethylphosphonate (22.37% mol total phosphorus), sodium ethylpropylphosphonate (63.31% mol total phosphorus), and sodium dipropylphosphonate (14.32% mol total phosphorus) (containing 0.1855 mol phosphorus) was mixed with a 30% aqueous solution containing 21.09 g of aluminum sulfate octadechydrate and 0.040 g of a 0.5% aqueous solution of copper sulfate pentahydrate. The reaction temperature was controlled at 70°C, resulting in a large amount of precipitate. The pH was adjusted to 3.0, and the reaction was stopped after 0.5 hours. The resulting reaction solution was filtered, and the filter cake was washed with deionized water until the pH was > 4.5. The filter cake was dried at 120°C to obtain 24.25 g of a white solid with the structure shown in formula (I) having x = 0.22, y = 0.64, z = 0.14, containing 2 ppm copper ions.

[0100] Example 9: Aluminum-copper hybrid salt of diethylphosphino-ethylpropylphosphino-dipropylphosphino containing 5 ppm copper ions (x=0.22, y=0.64, z=0.14) Following the method of Example 8, the mass of the copper sulfate pentahydrate aqueous solution was changed to 0.1 g, and everything else remained the same, resulting in 24.61 g of a white solid with the structure shown in formula (I) where x=0.22, y=0.64, z=0.14, containing 5 ppm of copper ions.

[0101] Example 10: A copper-diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid hybrid aluminum salt containing 11 ppm copper ions (x=0.22, y=0.64, z=0.14). Following the method of Example 8, the mass of the copper sulfate pentahydrate aqueous solution was changed to 0.2 g, and everything else remained the same, resulting in 24.25 g of a white solid with x=0.22, y=0.64, z=0.14 in the structure shown in Formula (I), containing 11 ppm of copper ions.

[0102] Example 11: A copper-diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid hybrid aluminum salt containing 28 ppm copper ions (x=0.22, y=0.64, z=0.14). Following the method of Example 8, the mass of the copper sulfate pentahydrate aqueous solution was changed to 0.6 g, and everything else remained the same, resulting in 24.58 g of a white solid with x=0.22, y=0.64, z=0.14 in the structure shown in Formula (I), containing 28 ppm of copper ions.

[0103] Example 12: A copper-diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid hybrid aluminum salt containing 47 ppm copper ions (x=0.22, y=0.64, z=0.14). Following the method of Example 8, the mass of the copper sulfate pentahydrate aqueous solution was changed to 1.0 g, and everything else remained the same, resulting in 24.29 g of a white solid with x=0.22, y=0.64, z=0.14 in the structure shown in Formula (I), containing 47 ppm of copper ions.

[0104] Example 13: A copper-diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid hybrid aluminum salt containing 98 ppm copper ions (x=0.22, y=0.64, z=0.14). Following the method of Example 8, 0.010 g of copper sulfate pentahydrate solid was used instead of its aqueous solution, and all other conditions were the same, to obtain 23.92 g of a white solid with x=0.22, y=0.64, z=0.14 in the structure shown in Formula (I), which contained 98 ppm of copper ions.

[0105] Example 14: A copper-diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid hybrid aluminum salt containing 480 ppm copper ions (x=0.22, y=0.64, z=0.14). Following the method of Example 8, 0.051 g of copper sulfate pentahydrate solid was used instead of its aqueous solution, and all other things were the same, to obtain 24.51 g of a white solid with x=0.22, y=0.64, z=0.14 in the structure shown in Formula (I), which contained 480 ppm of copper ions.

[0106] Example 15: Aluminum salt of diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid (x=0.41, y=0.55, z=0.04) A 71 g aqueous solution containing sodium diethylphosphonate (40.04% mol total phosphorus), sodium ethylpropylphosphonate (54.86% mol total phosphorus, including 5.06% mol ethyl isopropylphosphonate, 49.49% mol ethyl n-propylphosphonate and 0.31% dialkyl long-chain phosphonate), sodium dipropylphosphonate (3.49% mol total phosphorus), sodium propylphosphonate (0.25% mol total phosphorus), sodium ethylphosphonate (0.60% mol total phosphorus), sodium hypophosphite (0.12% mol total phosphorus), sodium phosphite (0.60% mol total phosphorus), and sodium phosphate (0.04% mol total phosphorus) (containing 0.1856 mol phosphorus) was mixed with a 30% aqueous solution containing 21.11 g of aluminum sulfate octadechydrate. The reaction temperature was controlled at 70°C, and the pH was adjusted to 3.0. A large amount of precipitate was obtained. After mixing, the mixture was kept at this temperature for 0.5 hours, and then the reaction was stopped. The resulting reaction solution was filtered, and the filter cake was washed with deionized water until the pH was greater than 4.5. The filter cake was dried at 120°C to obtain 23.20 g of a white solid with x=0.41, y=0.55, z=0.04 in formula (I) (containing impurities such as aluminum propylphosphonate, aluminum ethylphosphonate, aluminum phosphate, and aluminum phosphite, where x, y, and z are normalized values).

[0107] Example 16: Diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid hybrid aluminum iron salt containing 9 ppm iron ions (x=0.41, y=0.55, z=0.04) The mixture contains sodium diethylphosphonate (40.04% mol total phosphorus), sodium ethylpropylphosphonate (54.86% mol total phosphorus, including 5.06% mol ethyl isopropylphosphonate, 49.49% mol ethyl n-propylphosphonate and 0.31% mol dialkyl long-chain phosphonate), sodium dipropylphosphonate (3.49% mol total phosphorus), sodium propylphosphonate (0.25% mol total phosphorus), sodium ethylphosphonate (0.60% mol total phosphorus), and sodium hypophosphite (0.12% mol total phosphorus). 71 g of an aqueous solution of sodium phosphite (0.60% mol total phosphorus) and sodium phosphate (0.04% mol total phosphorus) (containing 0.1856 mol phosphorus) was mixed with a 30% aqueous solution containing 21.11 g of aluminum sulfate octahydrate and 0.15 g of a 0.5% aqueous solution of ferric chloride. The reaction temperature was controlled at 70°C, and the pH was adjusted to 3.0. A large amount of precipitate was obtained. After mixing, the mixture was kept at this temperature for 0.5 hours, and then the reaction was stopped. The resulting reaction solution was filtered, and the filter cake was washed with deionized water until the pH was > 4.5. The filter cake was dried at 120°C to obtain 22.40 g of a white solid with x = 0.41, y = 0.55, z = 0.04 in formula (I), containing 9 ppm of iron ions.

[0108] Example 17: Diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid hybrid aluminum iron salt containing 33 ppm iron ions (x=0.41, y=0.55, z=0.04) Following the method of Example 16, the mass of the ferric chloride aqueous solution was changed to 0.45 g, and everything else remained the same, resulting in 22.80 g of a white solid with x = 0.41, y = 0.55, z = 0.04 in formula (I), containing 33 ppm of iron ions.

[0109] Example 18: A copper-diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid hybrid aluminum salt containing 5 ppm copper ions (x=0.41, y=0.55, z=0.04). Following the method of Example 16, 0.15 g of 0.5% ferric chloride aqueous solution was replaced with 0.1 g of 0.5% copper sulfate pentahydrate aqueous solution, and everything else remained the same, resulting in 23.20 g of a white solid with x = 0.41, y = 0.55, z = 0.04 in formula (I), containing 5 ppm copper ions.

[0110] Example 19: A copper-diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid hybrid aluminum salt containing 10 ppm copper ions (x=0.41, y=0.55, z=0.04). Following the method of Example 16, 0.15 g of 0.5% ferric chloride aqueous solution was replaced with 0.20 g of 0.5% copper sulfate pentahydrate aqueous solution, and everything else remained the same, resulting in 22.90 g of a white solid with x = 0.41, y = 0.55, z = 0.04 in formula (I), containing 10 ppm copper ions.

[0111] Example 20: Aluminum salt of diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid (x=0.60, y=0.38, z=0.02) 71 g of an aqueous solution containing sodium diethylphosphonate (60.54% mol total phosphorus), sodium ethylpropylphosphonate (38.10% mol total phosphorus), and sodium dipropylphosphonate (1.36% mol total phosphorus) (containing 0.1788 mol phosphorus) was mixed with a 30% aqueous solution containing 20.34 g of aluminum sulfate octadecylhydrate. The reaction temperature was controlled at 70°C, and the pH was adjusted to 3.0. A large amount of precipitate was obtained. After mixing, the mixture was kept at this temperature for 0.5 hours, and then the reaction was stopped. The resulting reaction solution was filtered, and the filter cake was washed with deionized water until the pH was > 4.5. The filter cake was dried at 120°C to obtain 21.10 g of a white solid with x = 0.60, y = 0.38, and z = 0.02 in formula (I).

[0112] Example 21: A hybrid aluminum-iron salt of diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid containing 10 ppm iron ions (x=0.60, y=0.38, z=0.02). 71 g of an aqueous solution containing sodium diethylphosphonate (60.54% mol total phosphorus), sodium ethylpropylphosphonate (38.10% mol total phosphorus), and sodium dipropylphosphonate (1.36% mol total phosphorus) (containing 0.1788 mol phosphorus) was mixed with a 30% aqueous solution containing 20.34 g of aluminum sulfate octadecylhydrate and 0.14 g of a 0.5% aqueous solution of ferric chloride. The reaction temperature was controlled at 70°C, and the pH was adjusted to 3.0. A large amount of precipitate was obtained. After mixing, the mixture was kept at this temperature for 0.5 hours, and then the reaction was stopped. The resulting reaction solution was filtered, and the filter cake was washed with deionized water until the pH was > 4.5. The filter cake was dried at 120°C to obtain 19.81 g of a white solid with x = 0.60, y = 0.38, z = 0.02 in formula (I), containing 10 ppm of iron ions.

[0113] Example 22: Diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid hybrid aluminum iron salt containing 29 ppm iron ions (x=0.60, y=0.38, z=0.02) Following the method of Example 21, the mass of the ferric chloride aqueous solution was changed to 0.42 g, and everything else remained the same, resulting in 20.26 g of a white solid with x=0.60, y=0.38, z=0.02 in formula (I), containing 29 ppm of iron ions.

[0114] Example 23: A copper-diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid hybrid aluminum salt containing 5 ppm copper ions (x=0.60, y=0.38, z=0.02). Following the method of Example 21, 0.14 g of 0.5% ferric chloride aqueous solution was replaced with 0.095 g of 0.5% copper sulfate pentahydrate aqueous solution, and everything else remained the same, resulting in 19.90 g of a white solid with x=0.60, y=0.38, z=0.02 in formula (I), containing 5 ppm copper ions.

[0115] Example 24: A copper-diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid hybrid aluminum salt containing 10 ppm copper ions (x=0.60, y=0.38, z=0.02). Following the method of Example 21, 0.14 g of 0.5% ferric chloride aqueous solution was replaced with 0.19 g of 0.5% copper sulfate pentahydrate aqueous solution, and everything else remained the same, resulting in 20.00 g of a white solid with x=0.60, y=0.38, z=0.02 in formula (I), containing 10 ppm copper ions.

[0116] Example 25: Aluminum diethylphosphinate 71 g of sodium diethylphosphonate aqueous solution (containing 0.19 mol of phosphorus) was mixed with a 30% (w / w) aqueous solution containing 21.61 g of aluminum sulfate octahydrate. The reaction temperature was controlled at 70 °C, and the pH was adjusted to 3.0. A large amount of precipitate was obtained. After mixing was complete, the mixture was kept at this temperature for 0.5 hours, and then the reaction was stopped. The resulting reaction solution was filtered, and the filter cake was washed with deionized water until the pH was > 4.5. The filter cake was dried at 120 °C to obtain 21.18 g of white solid.

[0117] Example 26: Diethylphosphine-containing hybrid aluminum iron salt (x=1, y=0, z=0) containing 9 ppm iron ions 71 g of sodium diethylphosphonate aqueous solution (containing 0.19 mol of phosphorus) was mixed with a 30% (w / w) aqueous solution containing 21.61 g of aluminum sulfate octadecylhydrate and 0.143 g of a 0.5% (w / w) aqueous solution of ferric chloride. The reaction temperature was controlled at 70°C, and the pH was adjusted to 3.0. A large amount of precipitate was obtained. After mixing, the mixture was kept at this temperature for 0.5 hours, and then the reaction was stopped. The resulting reaction solution was filtered, and the filter cake was washed with deionized water until the pH was > 4.5. The filter cake was dried at 120°C to obtain 21.38 g of a white solid with x=1, y=0, z=0 in formula (I), containing 9 ppm of iron ions.

[0118] Example 27: Diethylphosphonic acid hybrid aluminum iron salt containing 30 ppm iron ions (x=1, y=0, z=0) Following the method of Example 26, the mass of the ferric chloride aqueous solution was changed from 0.143 g to 0.430 g, while everything else remained the same, resulting in 21.87 g of a white solid with x=1, y=0, z=0 in formula (I), containing 30 ppm of iron ions.

[0119] Example 28: Diethylphosphonic acid hybrid aluminum copper salt containing 5 ppm copper ions (x=1, y=0, z=0) Following the method of Example 26, the aqueous solution of ferric chloride was replaced with an aqueous solution of 0.095 g of copper sulfate pentahydrate with a mass concentration of 0.5%, and everything else remained the same, resulting in 21.74 g of a white solid with x=1, y=0, z=0 in formula (I), containing 5 ppm of copper ions.

[0120] Example 29: Diethylphosphonic acid hybrid aluminum copper salt containing 10 ppm copper ions (x=1, y=0, z=0) Following the method of Example 26, the aqueous solution of ferric chloride was replaced with an aqueous solution of 0.19 g of copper sulfate pentahydrate with a mass concentration of 0.5%, and everything else remained the same, resulting in 22.10 g of a white solid with x=1, y=0, z=0 in formula (I), containing 10 ppm of copper ions.

[0121] Example 30: Aluminum salt of diethylphosphonic acid-ethylisobutylphosphonic acid-diisobutylphosphonic acid (x=0.28, y=0.60, z=0.12) 93 g of an aqueous solution containing sodium diethylphosphonate (29.68% mol total phosphorus), sodium ethyl isobutylphosphonate (57.65% mol total phosphorus), and sodium diisobutylphosphonate (12.67% mol total phosphorus) (containing 0.10 mol of phosphorus) was mixed with a 30% aqueous solution containing 11.66 g of aluminum sulfate octadecylhydrate. The reaction temperature was controlled at 70°C, and the pH was adjusted to 3.0. A large amount of precipitate was obtained. After mixing, the mixture was kept at this temperature for 0.5 hours, and then the reaction was stopped. The resulting reaction solution was filtered, and the filter cake was washed with deionized water until the pH was > 4.5. The filter cake was dried at 120°C to obtain 14.50 g of white solid.

[0122] Example 31: Diethylphosphonic acid-ethylisobutylphosphonic acid-diisobutylphosphonic acid hybrid aluminum iron salt containing 10 ppm iron ions (x=0.28, y=0.60, z=0.12) Following the method of Example 30, 0.088 g of 0.5% ferric chloride aqueous solution was added to an aluminum sulfate aqueous solution, and finally 14.47 g of a white solid with formula (I) x=0.28, y=0.60, z=0.12 (x, y, z are normalized values) was obtained, which contained 10 ppm of iron ions.

[0123] Example 32: Preparation of diethylphosphine-ethylisobutylphosphine-diisobutylphosphine hybrid aluminum copper salt containing 10 ppm copper ions (x=0.28, y=0.60, z=0.12) Following the method of Example 30, 0.12 g of a 0.5% (w / w) aqueous solution of copper sulfate pentahydrate was added to an aluminum sulfate solution, and 14.49 g of a white solid with formula (I) x=0.28, y=0.60, z=0.12 was obtained, which contained 10 ppm of copper ions.

[0124] Example 33: Copper salt of diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid (x=0.22, y=0.64, z=0.14) 71 g of a mixed aqueous solution containing sodium diethylphosphonate (22.37% mol total phosphorus), sodium ethylpropylphosphonate (63.31% mol total phosphorus), and sodium dipropylphosphonate (14.32% mol total phosphorus) (containing 0.1855 mol total phosphorus) was mixed with a 30% aqueous solution containing 23.71 g of copper sulfate pentahydrate. The reaction temperature was controlled at 70 °C, resulting in a large amount of precipitate. The pH was adjusted to 4.0, and the reaction was stopped after 0.5 hours. The resulting reaction solution was filtered, and the filter cake was washed with deionized water until the pH was > 4.5. The filter cake was dried at 120 °C to obtain 27.15 g of a solid diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid copper salt (x = 0.22, y = 0.64, z = 0.14) with the structure shown in formula (I).

[0125] Example 34: Copper diethylphosphinate 71 g of sodium diethylphosphonate aqueous solution (containing 0.19 mol of phosphorus) was mixed with a 30% aqueous solution containing 24.29 g of copper sulfate pentahydrate. The reaction temperature was controlled at 70 °C, and the pH was adjusted to 4.0. A large amount of precipitate was obtained. After mixing was complete, the mixture was kept at this temperature for 0.5 hours, and then the reaction was stopped. The resulting reaction solution was filtered, and the filter cake was washed with deionized water until the pH was > 4.5. The filter cake was dried at 120 °C to obtain 25.6 g of copper diethylphosphonate.

[0126] The results of the muffle furnace test for the thermo-oxidative stability of the flame retardant are shown in the figure. Figures 1-5 .

[0127] from Figure 1 As can be seen, the thermo-oxidative stability of the diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid hybrid aluminum-copper salt (x=0.22, y=0.64, z=0.14) containing copper ions is much higher than that of the corresponding aluminum salt and the hybrid aluminum-iron salt with added iron ions. For example, the dialkylphosphonic acid hybrid aluminum-iron salt containing 49 ppm iron ions prepared in Example 4 turned gray to black after 18 minutes of high-temperature treatment, while the sample of Example 8 containing 2 ppm copper ions remained white after the same time. The sample of Example 7, containing 971 ppm iron ions, began to turn yellow after 22 minutes of high-temperature treatment and turned black after 30 minutes of high-temperature treatment. Its color was also far inferior to that of the sample of Example 10, which contained only 11 ppm copper ions and remained white or only slightly yellow after the same time.

[0128] Figure 2 This indicates that the thermo-oxidative stability of the diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid hybrid aluminum-copper salt (x=0.41, y=0.55, z=0.04) with copper ions is higher than that of the corresponding aluminum salt, and also higher than that of the hybrid aluminum-iron salt with added iron ions.

[0129] Figure 3 This indicates that the thermo-oxidative stability of the diethylphosphonic acid-ethylpropylphosphonic acid-dipropylphosphonic acid hybrid aluminum-copper salt (x=0.60, y=0.38, z=0.02) with copper ions is higher than that of the corresponding aluminum salt, and also higher than that of the hybrid aluminum-iron salt with added iron ions.

[0130] Figure 4 This indicates that the thermo-oxidative stability of the diethylphosphine hybrid aluminum copper salt (x=1, y=0, z=0) with the introduction of copper ions is higher than that of the corresponding aluminum salt and the hybrid aluminum iron salt with added iron ions.

[0131] Figure 5 This indicates that the thermo-oxidative stability of the diethylphosphino-ethylisobutylphosphino-diisobutylphosphino hybrid aluminum-copper salt (x=0.28, y=0.60, z=0.12) with copper ions is higher than that of the corresponding aluminum salt and the hybrid aluminum-iron salt with added iron ions.

[0132] Furthermore, even though copper diethylphosphonate is inherently blue, the introduction of copper ions not only enhances the thermo-oxidative stability of the dialkylphosphonic acid hybrid metal salt but also allows the product to retain the white color of aluminum dialkylphosphonate due to its extremely low dosage. Conversely, iron diethylphosphonate is inherently gray, and a relatively large amount of iron is required for a noticeable effect. Therefore, although the introduction of iron improves the thermo-oxidative stability of the dialkylphosphonic acid hybrid metal salt, the effect is poor, and it reduces the whiteness of the product, resulting in a visually inferior appearance.

[0133] The results of the heat resistance test of the flame retardant in TGA and the processing window results of the flame-retardant nylon are shown in Tables 1 and 2. The flame-retardant nylon consists of 87.5 parts of nylon 66 (containing 33% glass fiber) and 12.5 parts of dialkylphosphine hybrid aluminum salt. All flame-retardant nylons with added dialkylphosphine hybrid aluminum copper salt (x not equal to 1) achieved a UL 94 V-0 rating of 1.6 mm.

[0134] Table 1 .

[0135] Table 2 .

[0136] As shown in Tables 1 and 2, adding even trace amounts of copper ions can significantly improve the heat resistance of dialkylphosphine hybrid metal salts. At the same content, copper ions have a much greater effect on improving the heat resistance of flame retardants than iron ions, indicating that copper ions are more effective. For the same heat resistance of the flame retardant, the amount of copper ions used is several times lower than that of iron ions.

[0137] Tables 1 and 2 also demonstrate that the introduction of copper ions results in a wider processing window for flame-retardant nylon compared to flame-retardant nylon containing iron ions. The introduction of 2 ppm copper ions yields better results than 11 ppm iron ions, and the introduction of 11 ppm copper ions yields better results than 49 ppm iron ions. Other examples also show that the processing window for nylon using dialkylphosphine hybrid aluminum copper salt is higher than that of dialkylphosphine hybrid aluminum iron salt and hybrid dialkylphosphine aluminum or diethylphosphine aluminum without iron and copper ions.

[0138] Furthermore, by comparing the heat resistance of the flame retardants obtained in Examples 1, 33, and 8-14 in Table 1, and the heat resistance of the flame retardants obtained in Examples 25, 34, and 28-29 in Table 2, it can be seen that the heat resistance of copper dialkylphosphinate is weaker than that of aluminum dialkylphosphinate. However, the heat resistance of aluminum dialkylphosphinate can be significantly improved by introducing a small amount of copper ions at the ppm level into it, indicating that the hybrid aluminum-copper salt produces a synergistic enhancement effect.

[0139] from Figure 6 It can be seen that, regarding the color of the flame-retardant material, with the same amount of metal ions added, the flame-retardant nylon obtained in Example 11 (28 ppm copper ions) is lighter in color than the flame-retardant nylon with added metal ions in Example 3 (28 ppm iron ions) and the flame-retardant nylon without added metal (copper, iron) ions. Under similar flame retardant heat resistance, the flame-retardant nylon obtained in Example 11 (28 ppm copper ions) is lighter in color than the flame-retardant nylon with added metal ions in Example 6 (487 ppm iron ions), indicating that the introduction of copper ions results in a superior color for the flame-retardant material.

[0140] In summary, the introduction of copper ions at the ppm level into dialkylphosphinates not only improves the heat resistance and thermo-oxidative stability of the flame retardant itself, but also improves the thermo-oxidative stability of flame-retardant polymer materials, while also giving flame-retardant composite materials a better appearance and color.

[0141] All aspects, embodiments, and features of this invention should be considered illustrative in all respects and not limiting of the invention; the scope of the invention is defined only by the claims. Other embodiments, modifications, and uses will become apparent to those skilled in the art without departing from the spirit and scope of the invention as claimed.

[0142] In the preparation method of this invention, the order of the steps is not limited to the listed order. For those skilled in the art, variations in the order of the steps without creative effort are also within the scope of protection of this invention. Furthermore, two or more steps or actions can be performed simultaneously.

[0143] Finally, it should be noted that the specific embodiments described herein are merely illustrative examples of the invention and are not intended to limit the implementation of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them; it is neither necessary nor possible to exemplify all embodiments here. However, these obvious variations or modifications derived from the essential spirit of the invention still fall within the scope of protection of the invention, and interpreting them as any additional limitation would contradict the spirit of the invention.

Claims

1. A dialkylphosphine hybrid metal salt, characterized in that, The dialkylphosphine hybrid metal salt is selected from at least one of compounds having the chemical formula shown in formula (I): Equation (I), Among them, R1, R2, R3, R4, R5, and R6 may be the same or different, and each is independently selected from C1-C2. 18 Straight-chain or branched alkyl groups, C6–C 12 Aromatic group; 0 ≤ x, y, z ≤ 1, and x + y + z = 1; M is a metallic element, which is selected from at least one of Group IIA, Group IIIA, Group IVA, Group VA, transition metals other than copper, and lanthanides. n is the valence state of M, selected from 1, 2, 3 or 4; m represents the valence state of copper, selected from 1 or 2; 0.9975≤a≤0.9999999, 0.0000001≤b≤0.0025, and a+b=1.

2. The dialkylphosphine hybrid metal salt according to claim 1, characterized in that, R1, R2, R3, R4, R5, and R6 are each independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, neopentyl, sec-pentyl, tert-pentyl, n-hexyl, isohexyl, sec-hexyl, tert-hexyl, n-heptyl, isoheptyl, sec-heptyl, tert-heptyl, n-octyl, isooctyl, sec-octyl, tert-octyl, n-nonyl, sec-nonyl, tert-nonyl, n-decyl, isodel, sec-decyl, tert-decyl, n-undecyl, isoundecyl, sec-undecyl, tert-undecyl, n-dodecyl, isododecyl, sec-dodecyl, tert-dodecyl, and phenyl. And / or, the Group IIA metal element is selected from at least one of Be, Mg, Ca, Sr, Ba; the Group IIIA metal element is Al; the Group IVA metal element is Sn; the Group VA metal element is Sb; the transition metal element other than copper is selected from at least one of Fe, Zn, Ti, Zr, Mn; and the lanthanide metal element is Ce. And / or, the metallic element is Al, n=3.

3. The dialkylphosphine hybrid metal salt according to claim 1, characterized in that, R1, R2, R3, R4, R5, and R6 are each independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, and tert-butyl. Alternatively, R1, R2, R3, R4, R5, and R6 are each independently selected from ethyl, n-propyl, isopropyl, n-butyl, isobutyl, and tert-butyl. Alternatively, R1, R2, R3, R4, R5, and R6 are each independently selected from ethyl, n-propyl, isopropyl, n-butyl, and isobutyl. Alternatively, R1, R2, R3, R4, R5, and R6 are each independently selected from ethyl, n-propyl, and isopropyl.

4. The dialkylphosphine hybrid metal salt according to claim 1, characterized in that, 0.9985≤a≤0.999999, 0.000001≤b≤0.0015, and a+b=1; Alternatively, 0.999≤a≤0.999995, 0.000005≤b≤0.001, and a+b=1; Alternatively, 0.9995≤a≤0.999995, 0.000005≤b≤0.0005, and a+b=1; Alternatively, 0.99975≤a≤0.999995, 0.000005≤b≤0.00025, and a+b=1; Alternatively, 0.9998≤a≤0.99999, 0.00001≤b≤0.0002, and a+b=1; Alternatively, 0.99985≤a≤0.99998, 0.00002≤b≤0.00015, and a+b=1; Alternatively, 0.99991≤a≤0.99998, 0.00002≤b≤0.00009, and a+b=1; Alternatively, 0.99784≤a≤0.999991, 0.000009≤b≤0.00216, and a+b=1.

5. A method for preparing a dialkylphosphine hybrid metal salt as described in claim 1, characterized in that, The preparation method includes: The material containing a mixture of metal sources A and M and a copper source is reacted in an aqueous phase to obtain the dialkylphosphine hybrid metal salt; The mixture A contains R1-based and R2-based hypophosphonic acids and / or their alkali metal salts, R3-based and R4-based hypophosphonic acids and / or their alkali metal salts, and R5-based and R6-based hypophosphonic acids and / or their alkali metal salts.

6. The preparation method according to claim 5, characterized in that, The reaction conditions are: temperature 0~250℃, pressure 0.1~10MPa, and time 0.01~20h; And / or, the reaction is carried out at a pH of 0 to 5; And / or, the metal source M is one or more of the following: sulfate or hydrate of metal M, chloride or hydrate of metal M, nitrate or hydrate of metal M; And / or, the copper source is one or more of copper sulfate or its hydrate, copper chloride or its hydrate, copper oxide, copper hydroxide, copper nitrate or its hydrate, cuprous oxide, basic copper carbonate, cuprous chloride, and cuprous sulfide.

7. A flame retardant, characterized in that, The flame retardant is selected from at least one of the dialkylphosphonic acid hybrid metal salts according to any one of claims 1 to 4, and dialkylphosphonic acid hybrid metal salts prepared by the method according to claim 5 or 6.

8. A flame-retardant material, characterized in that, The flame-retardant material includes flame retardant P and thermoplastic polymer material; the flame retardant P is selected from at least one of the flame retardants as described in claim 7.

9. The flame-retardant material according to claim 8, characterized in that, The flame-retardant material contains 1-35 wt% flame retardant P; Alternatively, the flame-retardant material may contain 3-20 wt% flame retardant P.

10. The flame-retardant material according to claim 8, characterized in that, The flame retardant material also includes functional additives; the functional additives are selected from at least one of reinforcing agents, anti-dripping agents, stabilizers, pigments, dyes, char-forming catalysts, dispersants, nucleating agents, inorganic fillers, and antioxidants. And / or, the flame retardant material further includes a flame retardant Q; the flame retardant Q is selected from at least one of nitrogen-based flame retardants and boron-based flame retardants.

11. The flame-retardant material according to claim 10, characterized in that, The functional additives in the flame-retardant material have a mass content of 5-40%; And / or, the nitrogen-based flame retardant is selected from at least one of melamine cyanurate, melamine polyphosphate, and ammonium polyphosphate; And / or, the boron-based flame retardant is selected from zinc borate; And / or, the flame retardant Q has a mass content of 0.5-20% in the flame retardant material.

12. The flame-retardant material according to claim 8, characterized in that, The thermoplastic polymer material is selected from at least one of polyamide and polyester.

Citation Information

Patent Citations

  • Flame retardant mixtures, their preparation and uses

    CN107637605B

  • Two organic phosphinates, their preparation methods and uses

    CN107641136B